Breast cancer screening disparities among immigrant women by world region of origin: a population‐based study in Ontario, Canada. (22nd April 2016) - Vahabi, Mandana; Lofters, Aisha; Kumar, Matthew; Glazier, Richard H.
Abstract: Rates of mammography screening for breast cancer are disproportionately low in certain subgroups including low‐income and immigrant women. The purpose of the study was to examine differences in rates of appropriate breast cancer screening (i.e., screening mammography every 2 years) among Ontario immigrant women by world region of origin and explore the association between appropriate breast cancer screening among these women groups and individual and structural factors. A cohort of 183, 332 screening‐eligible immigrant women living in Ontario between 2010 and 2012 was created from linked databases and classified into eight world regions of origin. Appropriate screening rates were calculated for each region by age group and selected sociodemographic, immigration, and healthcare‐related characteristics. The association between appropriate screening across the eight regions of origin and selected sociodemographic, immigration, and health‐related characteristics was explored using multivariate Poisson regression. Screening varied by region of origin, with South Asian women (48.5%) having the lowest and Caribbean and Latin American women (63.7%) the highest cancer screening rates. Factors significantly associated with lower screening across the world regions of origin included living in the lowest income neighborhoods, having a refugee status, being a new immigrant, not having a regular physical examination, not being enrolled in a primary care patient enrollment model, having a male physician, and having an internationally trained physician. Multiple interventions entailing cross‐sector collaboration, promotion of patient enrollment models, community engagement, comprehensive and intensive outreach to women, and knowledge translation and transfer to physicians should be considered to address screening disparities among immigrant population. Consideration should be given to design and delivery of culturally appropriate and easily accessible cancer screening programs targeted at high‐ risk immigrant subgroups, such as women of South Asian origin, refugees, and new immigrants. Abstract : The study found differences in rates of breast cancer screening among Ontario immigrant women by world region of origin. South Asian women had the lowest cancer screening rates. Factors associated with lower screening included living in the lowest income neighborhoods, having a refugee status, being a new immigrant, not having a regular physical examination, not being enrolled in a primary care patient enrollment model, having a male physician, and having an internationally trained physician.